Designing an Infographic Poster for a Social Campaign Regarding Smartphone Addiction: English - Haviz Emriadi; Silvana Nurdiani; Muhammad Ghifari; Sri Meiweni Basra (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The purpose of this study is to design an infographic-based social campaign strategy as a form of representative effort against smartphone addiction in early childhood. This research method is based on qualitative descriptive. Using interviews and field study documentation as research data, this study analyzed the research subjects, parents who have early childhood experiences in Padang Panjang, using the SWOT method. Meanwhile, the object of this research is the visual communication design of social campaigns with the theme of smartphone addiction. The objective of this research can be achieved through four stages: data source analysis, exploration, planning, and realization. At the realization stage, three infographic posters were created, namely illustrations of children who passively use smartphones as a form of criticism of digital parenting patterns, infographic designs on the bad impact of smartphones on children, and tips so that children are not addicted to smartphones. This infographic poster is available in both print and digital forms, making it an efficient medium for conveying complex information on social media.